Rengginang Food Sold Out To Determine Customer Satisfaction - Nurpribadi, Giri; Rulianti, Erina (Proceeding International Pelita Bangsa, 2023)
Issue regarding global impact resilient on daily consumption.Food business need special treatment to develop some benefit,so that all activities in procurement factor about searching raw materials,food process engineering and supply chain management.Living with home industries with some production system through marketing system continuously need understanding with some measurement,One of some quality criterium regarding tangible quality such as thickness measurement and diameter measurement for meals.All activities about Sustainability Development Goals. Food innovative and creativity design as a think about carbohydrates and seasoning for ingredients going to process about rengginang traditional snacks food.Briefly, some food outlet had been sold some snacks with sold out for marketing terminology.It means,rengginang need quality management. Some Village in Bekasi Regency ,one of them in Sukabungah Village have got rengginang snacks food manufacturer. Customer Satisfaction as a respons about consumer preferences after sold out,need product design measurement.The most important asset of any organization is its customers.An organization’s success depend on how may customers it has,how much they buy,and how often they buy.Satisfied customers will increase,buy more,and buy more frequently.Increasingly, small scale production system are using customer satisfaction. Research Method by quantitative with Regression Equation.Preliminery Research with Observation use interview data,and data collecting using control chart to know adjustment needed for measurement accurately.This activity should be done as the first step in data analysis.If adjustment had be done,some data in process at SPSS statistical software,and some parameter such as t test and F test,Thickness Variable with t test 2.538 have got result 0.017 significantly,also significant with F test 3.276 have got result 0.053 simultaneously. Diameter with negative t test - 2.294 have got result 0.029.